EFEKTIVITAS METODE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Hilma Hilmatussa’diah; Muhammad Rizal; Ratu Dinny Fauziah; Abdul Kodir; Zahro Malihah (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2023)
Learning effectiveness is a measure related to the success rate of a learning process. The author categorizes the criteria for the effectiveness of learning methods in this study referring to student learning outcomes. When conducting observations, researchers found that many students' learning outcomes were not complete or many of their scores were still below the KKM. Due to this fact, the researcher was encouraged to use one of the TPS (Think Pair Share) type cooperative learning models. The purpose of this study was to determine the effectiveness of the Think Pair Share method on student PAI learning outcomes in the cognitive, affective and psychomotor domains of students. writer approached this research with a qualitative approach from a case study. The design of this research is class action or often called Classroom Action Research (PTK). With the results of class action research for 2 cycles using the TPS method and 1 pre-cycle using the lecture method, student learning outcomes have improved. The conclusion that can be drawn from the results of class action research to determine the effectiveness of the Think Pair Share method on PAI learning outcomes in class VI SDN Kotabatu 04 is that learning using the TPS method is said to be effective when compared to the lecture method that PAI teachers usually use in every PAI lesson, the results are clearly indicated by the achievement of the target student learning outcomes of more than 75% with indicators of success in improving learning outcomes in the cognitive, psychomotor and affective domains of class action research results.